Asian Affairs (JSTOR)
Asian Affairs: An American Review provides deep insight into developments in politics, economics, security, and international relations, especially between Asian nations and the United States. Scholars, educators, policymakers, government officials, and business executives can rely on its thoroughly researched articles. Recent articles examine South Korean civil society, Sino-Indian relations, and political developments in Turkmenistan. Book reviews by experts keep readers informed on current literature in the field.
Keywords: Asian Studies